10. Neurophysiological profile of multifocal motor neuropathy. Issue 3 (March 2016) - Garg, Nidhi; Park, Susanna B.; Pollard, John D.; Yiannikas, Con; Kiernan, Matthew C.
Abstract : Introduction: Multifocal motor neuropathy (MMN) is a rare immune-mediated neuropathy, typically presenting with asymmetrical, and slowly progressive, distal upper limb wasting and weakness without sensory abnormalities. The disorder is associated with GM1 antibodies in approximately 50% of cases but the pathogenic role of such antibodies along with the mechanism of conduction block remains unclear. Methods: Nerve conduction studies and motor axonal excitability studies were undertaken in 7 patients with MMN (mean age: 52.3). Axonal excitability studies were undertaken in the median nerve at the wrist and compared to 70 healthy controls (mean age: 49.6). Results: When compared healthy controls, patients with MMN had greater threshold changes in threshold electrotonus in both depolarizing (TEd 90–100 ms: 54.09  ±  1.3 vs 45.0  ±  0.5; p   <  0.01) and hyperpolarizing directions (TEh 90–100 ms: −157.7  ±  9.1 vs −117.8  ±  2.0; p   <  0.01). In addition, they demonstrated greater superexcitability (−40.2  ±  2.1 vs −23.7  ±  0.7; p   <  0.01) and reduced refractoriness at 2.5 msec (−6.7  ±  7.4 vs 28.2  ±  2.1; p   <  0.01). Conclusion: Patients with MMN have a unique neurophysiological profile demonstrated on axonal excitability studies which are consistent with axonal hyperpolarization.